Oceanic area system improvement study (OASIS) : final report - SRI International.; United States. Federal Aviation Administration. Office of Systems Engineering Management. (Washington, D.C. : The Office, 1981)
"September 1981." Cover title. v. 1. Executive summary and improvement alternatives development analysis / G.J. Couluris, B. Conrad -- v. 2. North Atlantic region air traffic services system description / G.J. Couluris -- v. 3. Central East Pacific region air traffic services system description / G.J. Couluris -- v. 4. Caribbean region air traffic services system description / G.J. Couluris -- v. 5. North Atlantic, Central East Pacific and Caribbean regions communication systems description / B. Conrad -- v. 7. North Atlantic region flight cost model results / G.J. Couluris, J.C. Bobick, J.D. Tornow -- v. 8. Central East Pacific region flight cost model results / D.B. Koretz, G.J. Couluris -- v. 9. Flight cost model description / K.Y. Wang, D.A. D'Esopo -- v. 10. North Atlantic, Central East Pacific and Caribbean regions aviation traffic forecasts / C. Starry, J.D. Tornow. Mode of access: Internet.